The Effects of Doa4 and Other Multivesicular-Body Proteins on Brome Mosaic Virus Replication in Yeast - Zaban, Nick (My University, 2008)
Brome Mosaic Virus (BMV) replication was measured in yeast single and double deletion mutants of Doa4 and other proteins in the multivesicular-body (MVB) pathway in order to determine the role of Doa4 and other MVB proteins in BMV replication. BMV is a positives-strand RNA virus that is studied as a model for many other RNA viruses. The MVB pathway packages proteins into endosomes and designates them for degradation. One MVB protein, Doa4, has been shown to affect BMV replication. Deletion mutants were transformed with plasmids encoding for BMV. Northern blotting and Western blotting were used to detect the accumulation of BMV RNAs and proteins in order to determine the degree of BMV replication in each mutant. One mutant containing the deletion of Doa4 and another MVB protein, Bro1, demonstrated BMV replication 60% of wild-type. This indicates that the deletion of Bro1 partially restores BMV replication when Doa4 is deleted.
20 p.
Keywords: Molecular Virology; Biochemistry